The Ashgate research companion to John Owen's theology - Kapic, Kelly M., 1972-; Jones, Mark, 1980- (Ashgate research companion., 2012)
John Owen (1616-1683) is regarded as one of the greatest theologians Britain ever produced. Owen has had an important historical and theological influence, and his significance is widely recognized today. As a revival in Owen studies and reprints has taken place, this much-needed companion by an international group of leading scholars, helpfully explores key questions related to Owen's method, theology, and pastoral practice. Examining his thought through such topics as his epic work on the Holy Spirit, his developed view of faith and reason, and his contribution to the place of toleration, this book offers an authoritative exploration of one of Britain's greatest theologians.